Role perception and role performance of elementary school principals in school health programs - Bituin, Remedios (Yap) 1914- ([Quezon City s.n.], 1974)
The proper functioning of the school health program hinges on the thorough understanding of the different roles each personnel member of the program has to play. To avoid conflicts, every role must be defined, the length and breadth of each understood. Such a need is imperative in the case of the principal, as an administrative officer of a school where the development of health programs take place. The aim of this study was to discover the perception of selected school officials on the roles of an elementary school principal in the school health program in the Division of Bulacan.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Elementary school principals -- Bulacan; School hygiene